ANALISIS PENGARUH PERIKLANAN DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI EKUITAS MEREK SEBAGAI VARIABEL INTERVENING PADA PRODUK NESCAFE DI KOTA SEMARANG - Primatika, Roza Azizah; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2018)
The purpose of this study to analyze Advertising and Sales Promotion on Brand Equity and the impact on Purchase Decision. The population of the study was all consumers who had ever done purchase transaction on Nescafe product, where respondents are Semarang people. The samples in this study were 120 respondents. The method of collecting data through questionnaires. This study uses analytical techniques of Structural Equation Modeling (SEM) with AMOS 22.0 as the analysis instrument.The result show that the Advertising has a positive and significant effect on Brand Equity, Sales Promotion has a positive and significant effect on Brand Equity, Advertising has a positive and significant effect on Purchase Decision, Sales Promotion has a negative impact on Purchase Decision, and Brand Equity has a positive and significant effect on Purchase Decision.